ADOBE FLASH MEDIA LEARNING ENGLISH THROUGH E-LEARNING SYSTEM IN UNIVERSITY OF MUHAMMADIYAH SUMATERA UTARA - Resty Wahyuni; Alfitriani Siregar; Rakhmat Wahyudin (JURNAL TARBIYAH, 2021)
The Objective of study is to find  the result of the learning process of Adobe Flash as media on the course of Pengembangan Media Pembelajaran through E-Learning system at English education study program in University of Muhammadiyah Sumatera Utara. E-learning provides a set of tools to enrich the value of conventional learning model, studies of textbooks, CD-ROMs, and computer-based training. Students can answer the challenges of globalization. Research Method used descriptive method through qualitative approach. Method of research conducted qualitative. Sample of research were forth semester students of English education study program. E learning system of UMSU provided schedule of course, attendance check, discussion forum between a lecture and students, task file, exercises file integrated Moodle and google form, module e book of Pengembangan Media Pembelajaran, slide file presentation, all activities viewed past, present and future time. Adobe flash media learning English implemented by virtual for one semester. The students can be active teaching English using Adobe Flash, simple material for presentation. They were enthusiastic when learn Adobe flash as media leaning English.